COMPARISON OF ABTS (2,2-AZINOBIS(3-ETHYLBENZOTHIAZOLINE)-6-SULFONIC ACID) AND DPPH (1,1-DIPHENYL-2-PICRYLHYDRAZYL) ASSAYS TO MEASURE THE ANTIOXIDANT ACTIVITY OF ETANOL EXTRACT OF RED ALGA (Gelidium sp) - Martiani, Isye; Rustamsyah, Ardi; Puspitasari, Tien Ellita Endah; Sujana, Dani (Faculty of Mathematic and Natural Science, Garut University, 2024)
Seaweeds have an ecological function as primary producers in marine waters. It also has an important economic value as a producer of hydrocolloids (alginate, agar, and carrageenan) used in various food and pharmaceutical industries. This study aims to determine the antioxidant activity of red algae (Gelidium sp). Extraction was done using the maceration method using 96% ethanol and concentrated by rotary evaporation. The antioxidant activity of the extract was tested using ABTS and DPPH methods. Antioxidant activity was seen from the IC50. The results showed that IC50 from ethanol extract of red algae (Gelidium sp) with the DPPH method is 3,9154 ppm. Then, using the ABTS method, IC50 from ethanol extract of red algae (Gelidium sp) is 9,1178 ppm. This result shows that the ethanol extract from red algae (Gelidium sp) has very strong antioxidant activity (<50 ppm).